Efficient low-carbon slurry curing agent and preparation method thereof

By using high-efficiency low-carbon curing agents prepared with raw materials such as polyacrylamide and modified hyperbranched polymers, the problems of high cost and unenvironmental protection of traditional curing agents are solved, and efficient and environmentally friendly mud curing effect is achieved.

CN119874318AActive Publication Date: 2025-04-25NANJING HYDRAULIC RES INST
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510346606.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-25
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

Traditional mud curing agents are costly, unenvironmental, and their coagulation speed and early strength are not ideal, which limits their wide application in the construction field.

Method used

High-efficiency low-carbon curing agent prepared by raw materials such as polyacrylamide, modified hyperbranched polymer, calcium carbonate, etc., improve the curing efficiency and water resistance of the curing agent by modifying the mesoporous structure and branched structure of the hyperbranched polymer.

Benefits of technology

It significantly improves the curing efficiency of the slurry curing agent, shortens the curing time, improves the strength and water resistance of the slurry after curing, reduces carbon emissions and environmental pollution, and has a certain environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses an efficient low-carbon slurry curing agent and a preparation method thereof. The mud curing agent prepared by the invention is prepared from the following raw materials in parts by weight: 5 to 10 parts of polyacrylamide, 10 to 15 parts of modified hyperbranched polymer, 1 to 3 parts of polyacrylate, 4 to 8 parts of calcium carbonate, 3 to 7 parts of calcium sulfate, 1 to 3 parts of sodium silicate, 10 to 12 parts of aluminum oxide and 3 to 6 parts of industrial waste residue. According to the curing agent, the curing efficiency of slurry is improved, the curing time is shortened, meanwhile, the strength and the water resistance of a cured slurry consolidated substance are improved, the curing efficiency can be improved through utilization of the industrial waste residues, and the effects of reducing the cost, achieving low carbon and being environmentally friendly can be achieved. Therefore, when the curing agent is used for curing slurry, carbon emission can be reduced, energy consumption and environmental pollution can be reduced, and the curing agent has certain environmental protection property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a mud high-efficiency low-carbon curing agent and a preparation method thereof. Background Art

[0002] The application of mud solidifiers is mainly aimed at the treatment of large amounts of waste mud generated in construction projects. With the rapid development of urbanization and infrastructure construction, the amount of waste mud generated in pile foundation projects, shield construction and other processes is huge. If not properly handled, it will cause serious pollution to the environment. Traditional treatment methods include direct discharge, safe stratum discharge, backfilling or sealing, but these methods all have environmental pollution risks or low efficiency. In order to solve these problems, researchers have developed mud solidification technology, which adds solidifiers to promote the particles in the mud to combine to form a stable solid structure, thereby reducing the impact on the environment and improving resource utilization. The application of mud solidification technology can not only reduce the generation of waste and reduce dependence on natural resources, but also convert waste mud into useful construction materials, such as roadbed fillers, foundation reinforcement materials, etc.

[0003] The selection of curing agent is crucial to the curing effect of mud. Traditional curing agents such as cement and lime have the problems of high cost and environmental pollution. Therefore, the development of new low-carbon soil curing cementitious materials has become a research hotspot. Most curing agents are based on the curing principle of inorganic gelling system. Their setting speed and early strength are still not ideal, and the potential for later strength growth is limited, which limits the application of curing agents in various fields. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a mud high-efficiency low-carbon curing agent and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A high-efficiency and low-carbon curing agent for mud, comprising the following raw materials in parts by weight: 5-10 parts of polyacrylamide, 10-15 parts of modified hyperbranched polymer, 1-3 parts of polyacrylate, 4-8 parts of calcium carbonate, 3-7 parts of calcium sulfate, 1-3 parts of sodium silicate, 10-12 parts of aluminum oxide, and 3-6 parts of industrial waste residue; The modified hyperbranched polymer is prepared by the following steps: Step A1, dispersing hexadecyltrimethylammonium bromide in deionized water, adding 0.1 mol / L hydrochloric acid and stirring for 20-30 min, then adding tetraethyl orthosilicate, and heating to 60-80° C. to react for 8-12 h, centrifuging, washing, and drying, collecting the product, and redispersing the product in an ethanolamine ethanol solution, and reflux extraction at 90° C. for 12 h, and then repeating the extraction once to obtain mesoporous silica; Step A2, dispersing toluene-2,5-diisocyanate and sodium hydroxide in toluene, adding γ-aminopropyltriethoxysilane, and heating to 70° C., reacting under nitrogen for 12-18 hours, rotary evaporating, collecting the product, and drying to obtain modified silane; Step A3, mixing the modified silane and triethylamine in toluene, adding mesoporous silica and ultrasonically dispersing for 30 minutes, and then condensing and refluxing at 110-120° C. for 2.5-3.5 hours, centrifuging, washing, and drying to obtain grafted modified silica; Step A4, dispersing the grafted modified silica and sodium hydroxide in toluene, heating to 60-70° C., adding ethylenediamine, reacting for 5-8 hours under nitrogen conditions, rotary evaporating, and collecting the intermediate product; re-dispersing the intermediate product in tetrahydrofuran, and then slowly adding it dropwise to trimethylolpropane triacrylate, reacting at 30-50° C. for 5-7 hours, and distilling under reduced pressure to obtain a terminal double-bond hyperbranched polymer; Step A5, after mixing the terminal double-bond hyperbranched polymer, sodium sulfite and sodium nitrate, heating to 80-90° C., then dropwise adding 0.05-0.08 mol / L sodium bisulfite aqueous solution, maintaining the temperature for reflux reaction for 8-10 hours, suction filtering, washing and drying to obtain a modified hyperbranched polymer; Further, in step A1, the usage ratio of hexadecyltrimethylammonium bromide, deionized water, hydrochloric acid, ethyl orthosilicate and ethanolamine ethanol solution is 0.6-0.9 g: 60 mL: 4-6 g: 3-4.5 mL: 100 mL; Further, in step A1, the volume ratio of ethanolamine to ethanol in the ethanolamine ethanol solution is 1:4; Further, in step A2, the usage ratio of toluene-2,5-diisocyanate, sodium hydroxide, toluene and γ-aminopropyltriethoxysilane is 0.015-0.03 mol: 0.01-0.05 g: 25-50 mL: 0.015-0.03 mol; Further, in step A3, the usage ratio of modified silane, triethylamine, toluene and mesoporous silica is 1-2 g: 5-10 mL: 100 mL: 3-5 g; Further, the amount ratio of grafted modified silica, sodium hydroxide, toluene and ethylenediamine in the intermediate product of step A4 is 1-3 g: 0.005-0.03 g: 100 mL: 0.008-0.02 mol; Further, the usage ratio of the intermediate product, tetrahydrofuran and trimethylolpropane triacrylate in the terminal double-bond hyperbranched polyester in step A4 is 1-3 g:100 mL:0.016-0.04 mol; Furthermore, in step A5, the usage ratio of the terminal double-bond hyperbranched polymer, sodium sulfite, sodium nitrate and sodium bisulfite aqueous solution is 1-3 g: 0.003-0.006 mol: 0.01-0.03 g: 100 mL.

[0006] A method for preparing a high-efficiency low-carbon curing agent for mud comprises the following steps: Weigh the raw materials by weight, add calcium carbonate, calcium sulfate, sodium silicate, aluminum oxide and industrial waste into a stirrer, stir evenly at a speed of 150-250rpm, then add polyacrylamide, modified hyperbranched polymer and polyacrylate, and stir evenly at a speed of 350-450rpm to obtain a high-efficiency and low-carbon curing agent for mud.

[0007] Beneficial effects of the present invention: The mud curing agent prepared by the present invention uses polyacrylamide and modified hyperbranched polymer as a matrix, adds water-absorbing resin, calcium carbonate and other curing aids, improves the curing efficiency of the curing agent on the mud, shortens the curing time, and also improves the strength and water resistance of the mud solid after curing, and the utilization of industrial waste residues can not only improve the curing efficiency, but also have the effects of reducing costs and being low-carbon and environmentally friendly. Therefore, when the curing agent is used for mud curing, carbon emissions can be reduced, energy consumption and environmental pollution can be reduced, and it has certain environmental protection.

[0008] As a water-absorbing resin, polyacrylic acid resin can work together with calcium sulfate to quickly and efficiently remove water molecules between particles in the mud and reduce the moisture inside the mud solids; calcium carbonate can significantly increase the solid content in the mud by reacting exothermically with the water in the mud to generate calcium hydrates or calcium hydroxide. This process not only increases the solid content of the sludge, but also increases the system temperature under the action of the heat released by the hydration reaction, which helps to sterilize and reduce pathogenic microorganisms and achieve harmless treatment of the mud.

[0009] In the modified hyperbranched polymer, hexadecyltrimethylammonium bromide is used as a template agent and tetraethyl orthosilicate is used as a silicon source to prepare mesoporous silica; then, a modified silane containing terminal isocyanate groups is synthesized by a condensation reaction between an isocyanate group in toluene-2,5-diisocyanate and an amino group in γ-aminopropyltriethoxysilane; then, the modified silane is used as a grafting modifier to carry out surface grafting on the mesoporous silica to obtain a grafted modified silica containing isocyanate groups on the surface; then, the isocyanate groups in the grafted modified silica are reacted with ethylenediamine to obtain an intermediate product containing a urea bond, and the amino group in the intermediate product can also react with a double bond in trimethylolpropane triacrylate to generate a terminal double-bond hyperbranched polymer containing a double bond structure at the terminal; finally, the terminal double-bond hyperbranched polymer is sulfonated to synthesize the modified hyperbranched polymer. The introduction of modified hyperbranched polymers can improve the water resistance and curing efficiency of the curing agent and shorten the curing time. The sulfonic acid group at the end of the polymer exists in the mud in the form of negative charge, and can adsorb metal cations in the mud to form larger agglomerates, thereby causing the metal ions to precipitate, greatly promoting the flocculation effect and improving the curing efficiency. The hyperbranched polymer with a core-shell structure can utilize its unique three-dimensional spherical structure and the active groups on the shell side chains to interact with the mud particles to form a three-dimensional network structure in the mud, thereby improving the curing efficiency and performance of the mud. At the same time, the mesoporous silica in the core layer can also utilize the mesoporous structure to adsorb heavy metals in the mud and reduce the heavy metal content. In addition, the urea bond in the side chain structure has excellent water resistance, which can effectively improve the waterproof performance of the curing agent, so that the solidified body after the mud is filtered remains stable in a humid or underwater environment without secondary mudification. DETAILED DESCRIPTION

[0010] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0011] Example 1 The modified hyperbranched polymer is prepared by the following steps: Step A1, 0.6g of hexadecyltrimethylammonium bromide is dispersed in 60mL of deionized water, 4g of 0.1mol / L hydrochloric acid is added and stirred for 20min, then 3mL of tetraethyl orthosilicate is added, and the temperature is raised to 60°C for reaction for 8h, centrifuged, washed, dried, and the product is collected, and the product is redispersed in 100mL of ethanolamine ethanol solution, and refluxed and extracted at 90°C for 12h, and the extraction is repeated once to obtain mesoporous silica, wherein the volume ratio of ethanolamine to ethanol in the ethanolamine ethanol solution is 1:4; Step A2, dispersing 0.015 mol toluene-2,5-diisocyanate and 0.01 g sodium hydroxide in 25 mL toluene, adding 0.015 mol γ-aminopropyltriethoxysilane, heating to 70° C., reacting under nitrogen for 12 h, rotary evaporation, collecting the product, and drying to obtain modified silane; Step A3, 1 g of modified silane and 5 mL of triethylamine were mixed in 100 mL of toluene, and then 3 g of mesoporous silica was added for ultrasonic dispersion for 30 min, and then condensed and refluxed at 110° C. for 2.5 h, centrifuged, washed, and dried to obtain grafted modified silica; Step A4, dispersing 1 g of grafted modified silica and 0.005 g of sodium hydroxide in 100 mL of toluene, heating to 60° C., adding 0.008 mol of ethylenediamine, reacting for 5 h under nitrogen, rotary evaporating, and collecting the intermediate product; re-dispersing 1 g of the intermediate product in 100 mL of tetrahydrofuran, then slowly dropping it into 0.016 mol of trimethylolpropane triacrylate, reacting at 30° C. for 5 h, and distilling under reduced pressure to obtain a terminal double-bond hyperbranched polymer; Step A5, after mixing 1 g of a double-bond-terminated hyperbranched polymer, 0.003 mol of sodium sulfite and 0.01 g of sodium nitrate, the mixture was heated to 80° C., and 100 mL of a 0.05 mol / L sodium bisulfite aqueous solution was added dropwise, the temperature was maintained under reflux for 8 h, and the mixture was filtered, washed and dried to obtain a modified hyperbranched polymer.

[0012] Example 2 The modified hyperbranched polymer is prepared by the following steps: Step A1, 0.75g of hexadecyltrimethylammonium bromide is dispersed in 60mL of deionized water, 5g of 0.1mol / L hydrochloric acid is added and stirred for 25min, then 4mL of tetraethyl orthosilicate is added, and the temperature is raised to 70°C for reaction for 10h, centrifuged, washed, dried, and the product is collected, and the product is redispersed in 100mL of ethanolamine ethanol solution, and refluxed and extracted at 90°C for 12h, and the extraction is repeated once to obtain mesoporous silica, wherein the volume ratio of ethanolamine to ethanol in the ethanolamine ethanol solution is 1:4; Step A2, dispersing 0.02 mol toluene-2,5-diisocyanate and 0.03 g sodium hydroxide in 35 mL toluene, adding 0.02 mol γ-aminopropyltriethoxysilane, heating to 70° C., reacting under nitrogen for 15 h, rotary evaporation, collecting the product, and drying to obtain modified silane; Step A3, 1.5 g of modified silane and 7.5 mL of triethylamine were mixed in 100 mL of toluene, and 4 g of mesoporous silica was added for ultrasonic dispersion for 30 min, and then condensed and refluxed at 115° C. for 3 h, centrifuged, washed, and dried to obtain grafted modified silica; Step A4, dispersing 2 g of grafted modified silica and 0.015 g of sodium hydroxide in 100 mL of toluene, heating to 65° C., adding 0.012 mol of ethylenediamine, reacting for 6 h under nitrogen conditions, rotary evaporation, and collecting the intermediate product; re-dispersing 2 g of the intermediate product in 100 mL of tetrahydrofuran, and then slowly adding dropwise to 0.025 mol of trimethylolpropane triacrylate, reacting at 40° C. for 6 h, and distilling under reduced pressure to obtain a terminal double-bond hyperbranched polymer; Step A5, 2 g of a double-bond-terminated hyperbranched polymer, 0.0045 mol of sodium sulfite, and 0.02 g of sodium nitrate were mixed, the temperature was raised to 85° C., 100 mL of a 0.065 mol / L sodium bisulfite aqueous solution was added dropwise, the temperature was maintained under reflux for 9 h, suction filtered, washed, and dried to obtain a modified hyperbranched polymer.

[0013] Example 3 The modified hyperbranched polymer is prepared by the following steps: Step A1, 0.9 g of hexadecyltrimethylammonium bromide was dispersed in 60 mL of deionized water, 6 g of 0.1 mol / L hydrochloric acid was added and stirred for 30 min, and then 4.5 mL of tetraethyl orthosilicate was added, and the temperature was raised to 80° C. for reaction for 12 h, centrifuged, washed, and dried, and the product was collected, and the product was redispersed in 100 mL of ethanolamine ethanol solution, and refluxed and extracted at 90° C. for 12 h, and the extraction was repeated once to obtain mesoporous silica, and the volume ratio of ethanolamine to ethanol in the ethanolamine ethanol solution was 1:4; Step A2, dispersing 0.03 mol toluene-2,5-diisocyanate and 0.05 g sodium hydroxide in 50 mL toluene, adding 0.03 mol γ-aminopropyltriethoxysilane, and heating to 70° C., reacting under nitrogen for 18 h, rotary evaporation, collecting the product, and drying to obtain modified silane; Step A3, 2 g of modified silane and 10 mL of triethylamine were mixed in 100 mL of toluene, and then 5 g of mesoporous silica was added for ultrasonic dispersion for 30 min, and then condensed and refluxed at 120° C. for 3.5 h, centrifuged, washed, and dried to obtain grafted modified silica; Step A4, dispersing 3 g of grafted modified silica and 0.03 g of sodium hydroxide in 100 mL of toluene, heating to 70° C., adding 0.02 mol of ethylenediamine, reacting for 8 h under nitrogen conditions, rotary evaporation, and collecting the intermediate product; re-dispersing 3 g of the intermediate product in 100 mL of tetrahydrofuran, and then slowly adding dropwise to 0.04 mol of trimethylolpropane triacrylate, reacting at 50° C. for 7 h, and distilling under reduced pressure to obtain a terminal double-bond hyperbranched polymer; Step A5, 3 g of a double-bond-terminated hyperbranched polymer, 0.006 mol of sodium sulfite, and 0.03 g of sodium nitrate were mixed, the temperature was raised to 90° C., 100 mL of a 0.08 mol / L sodium bisulfite aqueous solution was added dropwise, the temperature was maintained under reflux for 10 h, suction filtered, washed, and dried to obtain a modified hyperbranched polymer.

[0014] Example 4 A method for preparing a high-efficiency low-carbon curing agent for mud comprises the following steps: 5 parts of polyacrylamide, 10 parts of the modified hyperbranched polymer prepared in Example 1, 1 part of polyacrylate, 4 parts of calcium carbonate, 3 parts of calcium sulfate, 1 part of sodium silicate, 10 parts of aluminum oxide, and 3 parts of blast furnace slag; Weigh the raw materials by weight, add calcium carbonate, calcium sulfate, sodium silicate, aluminum oxide and blast furnace slag into a stirrer, stir evenly at a speed of 150 rpm, then add polyacrylamide, the modified hyperbranched polymer prepared in Example 1 and polyacrylate, and stir evenly at a speed of 350 rpm to obtain a high-efficiency and low-carbon curing agent for mud.

[0015] Example 5 A method for preparing a high-efficiency low-carbon curing agent for mud comprises the following steps: 7 parts of polyacrylamide, 12 parts of the modified hyperbranched polymer prepared in Example 2, 2 parts of polyacrylate, 6 parts of calcium carbonate, 5 parts of calcium sulfate, 2 parts of sodium silicate, 11 parts of aluminum oxide, and 5 parts of blast furnace slag; Weigh the raw materials by weight, add calcium carbonate, calcium sulfate, sodium silicate, aluminum oxide and blast furnace slag into a stirrer, stir evenly at a speed of 200 rpm, then add polyacrylamide, the modified hyperbranched polymer prepared in Example 2 and polyacrylate, and stir evenly at a speed of 400 rpm to obtain a high-efficiency and low-carbon curing agent for mud.

[0016] Example 6 A method for preparing a high-efficiency low-carbon curing agent for mud comprises the following steps: 10 parts of polyacrylamide, 15 parts of the modified hyperbranched polymer prepared in Example 3, 3 parts of polyacrylate, 8 parts of calcium carbonate, 7 parts of calcium sulfate, 3 parts of sodium silicate, 12 parts of aluminum oxide, and 6 parts of blast furnace slag; Weigh the raw materials by weight, add calcium carbonate, calcium sulfate, sodium silicate, aluminum oxide and blast furnace slag into a stirrer, and stir evenly at a speed of 250 rpm, then add polyacrylamide, the modified hyperbranched polymer prepared in Example 3 and polyacrylate, and stir evenly at a speed of 450 rpm to obtain a high-efficiency and low-carbon curing agent for mud.

[0017] Comparative Example 1 This comparative example is a mud curing agent, which is different from Example 6 in that commercially available hyperbranched polyester is used instead of the modified hyperbranched polymer prepared in Example 3, and the rest are the same.

[0018] Comparative Example 2 This comparative example is a mud curing agent, which differs from Example 6 in that silicon dioxide replaces calcium carbonate, and the rest is the same.

[0019] A solidification experiment was conducted on a certain waste mud (water content of 85.8%), and the amount of the added curing agent (prepared in Examples 4-6 and Comparative Examples 1-2) was 5% of the mud mass. The mud was treated and the solidified mud was tested in accordance with "GB5085.03-2019 Hazardous Waste Identification Standard-Leaching Toxicity Identification" and "GB / T50123-2019 Geotechnical Test Method Standard"; The test results are shown in the following table: It can be seen from the above table that after the mud is treated with the mud curing agent prepared by the present invention, the 14d water content of the mud solidified material is in the range of 23.9%-24.6%, the 28d unconfined compressive strength is in the range of 1.55MPa-1.60MPa, and the strength loss rate after 10 freeze-thaw cycles after 28d is in the range of 15.2%-15.5%, indicating that the use of the curing agent can significantly improve the curing efficiency, waterproof performance, and consolidation strength of the mud, and reduce carbon emissions, energy consumption, and environmental pollution, and has certain environmental protection.

[0020] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high-efficiency low-carbon curing agent for mud, characterized in that: The invention comprises the following raw materials in parts by weight: 5-10 parts of polyacrylamide, 10-15 parts of modified hyperbranched polymer, 1-3 parts of polyacrylate, 4-8 parts of calcium carbonate, 3-7 parts of calcium sulfate, 1-3 parts of sodium silicate, 10-12 parts of aluminum oxide and 3-6 parts of industrial waste residue; The modified hyperbranched polymer is prepared by the following steps: Step A1, dispersing hexadecyltrimethylammonium bromide in deionized water, adding 0.1 mol / L hydrochloric acid and stirring for 20-30 min, then adding tetraethyl orthosilicate, and heating to 60-80° C. to react for 8-12 h, centrifuging, washing, and drying, collecting the product, and redispersing the product in an ethanolamine ethanol solution, and reflux extraction at 90° C. for 12 h, and then repeating the extraction once to obtain mesoporous silica; Step A2, dispersing toluene-2,5-diisocyanate and sodium hydroxide in toluene, adding γ-aminopropyltriethoxysilane, and heating to 70° C., reacting under nitrogen for 12-18 hours, rotary evaporating, collecting the product, and drying to obtain modified silane; Step A3, mixing the modified silane and triethylamine in toluene, adding mesoporous silica and ultrasonically dispersing for 30 minutes, and then condensing and refluxing at 110-120° C. for 2.5-3.5 hours, centrifuging, washing, and drying to obtain grafted modified silica; Step A4, dispersing the grafted modified silica and sodium hydroxide in toluene, heating to 60-70° C., adding ethylenediamine, reacting for 5-8 hours under nitrogen conditions, rotary evaporating, and collecting the intermediate product; re-dispersing the intermediate product in tetrahydrofuran, and then slowly adding it dropwise to trimethylolpropane triacrylate, reacting at 30-50° C. for 5-7 hours, and distilling under reduced pressure to obtain a terminal double-bond hyperbranched polymer; Step A5, after mixing the terminal double-bond hyperbranched polymer, sodium sulfite and sodium nitrate, heating to 80-90° C., then dropwise adding 0.05-0.08 mol / L sodium bisulfite aqueous solution, maintaining the temperature for reflux reaction for 8-10 hours, filtering, washing and drying to obtain the modified hyperbranched polymer.

2. A high-efficiency low-carbon mud curing agent according to claim 1, characterized in that: In step A1, the usage ratio of hexadecyltrimethylammonium bromide, deionized water, hydrochloric acid, ethyl orthosilicate and ethanolamine ethanol solution is 0.6-0.9 g: 60 mL: 4-6 g: 3-4.5 mL: 100 mL.

3. A high-efficiency low-carbon mud curing agent according to claim 1, characterized in that: The volume ratio of ethanolamine to ethanol in the ethanolamine ethanol solution in step A1 is 1:

4.

4. The high-efficiency and low-carbon slurry curing agent according to claim 1, characterized in that: In step A2, the usage ratio of toluene-2,5-diisocyanate, sodium hydroxide, toluene and γ-aminopropyltriethoxysilane is 0.015-0.03 mol: 0.01-0.05 g: 25-50 mL: 0.015-0.03 mol.

5. The high-efficiency and low-carbon curing agent for mud according to claim 1, characterized in that: The usage ratio of grafted modified silica, sodium hydroxide, toluene and ethylenediamine in the intermediate product of step A4 is 1-3 g: 0.005-0.03 g: 100 mL: 0.008-0.02 mol.

6. The high-efficiency and low-carbon curing agent for mud according to claim 1, characterized in that: In step A4, the usage ratio of the intermediate product, tetrahydrofuran and trimethylolpropane triacrylate in the terminal double-bond hyperbranched polyester is 1-3 g:100 mL:0.016-0.04 mol.

7. The high-efficiency and low-carbon curing agent for mud according to claim 1, characterized in that: In step A5, the usage ratio of the terminal double-bond hyperbranched polymer, sodium sulfite, sodium nitrate and sodium bisulfite aqueous solution is 1-3 g: 0.003-0.006mol: 0.01-0.03g: 100mL.

8. The high-efficiency and low-carbon slurry curing agent according to claim 1, characterized in that: The industrial waste slag is one or both of blast furnace slag and fly ash.

9. A method for preparing the high-efficiency low-carbon curing agent for mud according to any one of claims 1 to 8, characterized in that: The following steps are involved: Weigh the raw materials by weight, add calcium carbonate, calcium sulfate, sodium silicate, aluminum oxide and industrial waste into a stirrer, stir evenly at a speed of 150-250rpm, then add polyacrylamide, modified hyperbranched polymer and polyacrylate, and stir evenly at a speed of 350-450rpm to obtain a high-efficiency and low-carbon curing agent for mud.

Citation Information

Patent Citations

  • Environment-friendly type soil solidifying agent

    CN101100854A

  • Sulfonate surfactant and preparation method thereof

    CN102690641A

  • Novel environment-friendly composite curing agent and application thereof

    CN111607405A

  • Powdery soil stabilizer as well as preparation method and application thereof

    CN116286012A

  • Low-carbon composite gelling curing agent for curing silt soft soil and curing method of low-carbon composite gelling curing agent

    CN118026634A